Implementation of Emergency Team Management Activation and Code Blue in Regional General Hospitals: Case Study - Faizatiwahida, Novia; Irnu, Julfilkar Adnan; Rukhama, Rafi Achmad; Hemu, Viky Noviani; Suprayogi, Suprayogi; Alfrisa, Bagus; Wahyudi, Purnomo; Setyobudi, Hari; Triatmojo, Setyo; Setiyarini, Sri; Kusuma, Happy Indah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Regional general hospitals, as the first line of healthcare services, still face the challenge of high patient mortality and morbidity rates. Efforts to reduce these rates can be achieved through the implementation of the Team Medical Emergency (TME) and Code Blue systems as early detection mechanisms and rapid response to emergency situations. This study aims to determine the implementation of TME and Code Blue at Dr. Soedirman Regional General Hospital, Kebumen. The research method used a case study design with secondary data collected from May 2022 to February 2023. Data were analyzed to determine the distribution of TME and Code Blue activations based on case type, gender, and service unit. The results showed that TME and Code Blue activations were most common in patients with internal medicine cases, male patients, and in adult inpatient wards. These findings indicate that the implementation of the TME and Code Blue systems is significantly influenced by factors such as case type, patient characteristics, and treatment location. The general implications of this study are the need to optimize healthcare worker training, strengthen early detection systems, and continuously evaluate TME and Code Blue implementation to reduce mortality and morbidity in regional hospitals.